GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 14951 species occurrences available in GBIF matching the query: TaxonKey: Felis silvestris Schreber, 1777. The dataset includes 14951 records from 154 constituent datasets: 4 records from National Biodiversity Data Bank. Observation records, 1900-2014. 14 records from Ghent University - Zoology Museum - Vertebrate collection. 2 records from SUI Vertebrate Collection. 2 records from ISM Mammalogy Collection. 158 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 7 records from UConn Mammals. 39 records from MVZ Mammal Collection (Arctos). 35 records from Zoology (Museum of Evolution - Uppsala). 1 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 224 records from BioGIS - Mammals - INPA database. 13 records from KUBI Mammalogy Collection. 19 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 1788 records from Inventario Español de Especies Terrestres (MAGRAMA). 3 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 1206 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 1 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 1 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 9 records from CUMV Mammal Collection (Arctos). 1 records from UAM Mammal Collection (Arctos). 175 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Museum Victoria provider for OZCAM. 153 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 273 records from Field Museum of Natural History (Zoology) Mammal Collection. 31 records from MVZ Hildebrand Collection (Arctos). 6 records from Lund Museum of Zoology (MZLU). 246 records from Données ONF Faune-Flore-Fonge. 5 records from Creación de la base de datos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, y de la reserva de la biosfera Islas del Golfo de California para el grupo de los mamíferos. 17 records from Naturalis Biodiversity Center (NL) - Mammalia. 2 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 19 records from iNaturalist Research-grade Observations. 21 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 29 records from Mammals housed at MHNG, Geneva. 10 records from Census of the animals of Benin. 21 records from BioGIS - Mammals - SPNI. 6 records from DMNS Mammal Collection (Arctos). 42 records from Mammal collection, Natural History Museum, University of Oslo. 1788 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 581 records from naturgucker. 16 records from Vertebrats d'Andorra. 27 records from CAS Mammalogy (MAM). 7 records from UMMZ Mammal Collection. 185 records from BioGIS - Hamaarag. 6 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 19 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 238 records from MfN - Fossil vertebrates IV. 6 records from SBMNH Vertebrate Zoology. 1 records from Northern Territory Museum and Art Gallery provider for OZCAM. 54 records from LACM Vertebrate Collection. 2 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 13 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 67 records from Natural History Museum (London) Collection Specimens. 3 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 108 records from NMNH Extant Specimen and Observation Records. 12 records from Collection Anatomie Histologie - SMF. 5 records from UWBM Mammalogy Collection. 11 records from NYSM Mammals. 5 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 19 records from Museo Nacional de Ciencias Naturales, Colección de Mamíferos: MNCN-Mam. 4 records from LSUMZ Mammals Collection. 19 records from Paleobiology Database. 1 records from Mammal collection of National Museum of Nature and Science. 1 records from Mammals Specimens. 3 records from FHSM Mammals Collection. 3577 records from Inventaire National du Patrimoine Naturel : Enquête carnivores. 12 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 1 records from TTU Mammals Collection. 423 records from Israel Nature and Parks Authority. 523 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 1 records from Schulhof Bühlschule Giengen. 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Schulhof und Anlagensee in Nellingen. 312 records from HBRG Vertebrates (not Badger) Dataset. 2 records from Occurrence of mammalia relicts at site Pestera Cioarei. 1 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 1 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 2 records from Occurrence of mammalia relicts at site Malerfels_I. 2 records from Occurrence of mammalia relicts at site Bocksteingrotte/Lonetal. 2 records from Occurrence of mammalia relicts at site Raj Cave. 3 records from Occurrence of mammalia relicts at site la Grotte du Thai. 19 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 2 records from Occurrence of mammalia relicts at site Krapina. 1 records from Occurrence of mammalia relicts at site Sveduv stul. 1 records from Occurrence of mammalia relicts at site Rusenschloß. 4 records from Occurrence of mammalia relicts at site Veternica. 2 records from Occurrence of mammalia relicts at site Velika Pecina. 2 records from Occurrence of mammalia relicts at site Vindija. 1 records from Occurrence of mammalia relicts at site Sandalja II. 2 records from Occurrence of mammalia relicts at site Kalman Lambrecht Cave. 1 records from Occurrence of mammalia relicts at site Istalloskö. 3 records from Occurrence of mammalia relicts at site Remetehegy. 2 records from Occurrence of mammalia relicts at site Remetehegy. 1 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 2 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 7 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 2 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 3 records from Occurrence of mammalia relicts at site Sirgenstein. 2 records from Occurrence of mammalia relicts at site Ettingen. 1 records from Occurrence of mammalia relicts at site la Grotte des Fees. 1 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 1 records from Occurrence of mammalia relicts at site Nietoperzowa. 2 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 2 records from Occurrence of mammalia relicts at site l´Abri du Morin. 1 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 1 records from Occurrence of mammalia relicts at site Pavlov. 3 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 2 records from Occurrence of mammalia relicts at site Pecurski Karnen. 1 records from Occurrence of mammalia relicts at site Oelknitz. 2 records from Occurrence of mammalia relicts at site Pestera Cioarei. 1 records from Occurrence of mammalia relicts at site Erdhöhle. 2 records from Occurrence of mammalia relicts at site Biedermann. 1 records from Occurrence of mammalia relicts at site Burgtonna. 2 records from Occurrence of mammalia relicts at site Spitalhöhle. 1 records from Occurrence of mammalia relicts at site Grotte Scladina. 1 records from Occurrence of mammalia relicts at site Icoana. 1 records from Occurrence of mammalia relicts at site Schweizerbild. 2 records from Occurrence of mammalia relicts at site Fuchsenloch. 1 records from Occurrence of mammalia relicts at site Felslindlhöhle. 1 records from Occurrence of mammalia relicts at site Einhornhöhle. 2 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 10 records from Census of the threatened species of Benin. Data mobilized in the framework of BID-AF2015-0066-REG project funded by EU. 1 records from Natural History Museum, University of Tartu. 240 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 298 records from Biological and palaeontological collection and observation data MNHNL. 304 records from Collection Mammalia SMF. 184 records from AMNH Mammal Collections. 83 records from Ditsong National Museum of Natural History Collection: 1805-2008. 253 records from ArtenFinder. 3 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 1 records from BioGIS - Mammals - HUJ collections. 6 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 5 records from MSB Mammal Collection (Arctos). 12 records from MSB Host Collection (Arctos). 163 records from Animal Sound Archive. 2 records from Bernice P. Bishop Museum. 8 records from Mammalogy Collection - Royal Ontario Museum. 322 records from Large mammals in Israel from camera traps. 246 records from Données ONF Faune-Flore-FOnge. 4 records from Collection Paleoanthropology SMF. 2 records from National System of Protected Areas in Poland - Animals. 2 records from Australian Museum provider for OZCAM. 28 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa).. 2 records from Anymals+plants - Citizen Science Data. 1 records from NCSM Mammals Collection. 1 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 16 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 4 records from Data collected on scitizen science web portal www.ornitho.cat. 3 records from Collection Mammalogie - ZSRO. 2 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences